Blessedly forgetful and blissfully unaware: a positivity bias in memory for (re)constructions of imagined past and future events. Issue 7 (8th August 2020) - Ünal, Belgin; Besken, Miri
ABSTRACT: People frequently consider the alternatives of the events that can happen in the future and of the events that already happened in the past in everyday life. The current study investigates the effects of engaging in imagination of hypothetical future (Experiment 1) and past (Experiment 2) events on memory and metamemory. We demonstrate, across two experiments, that imagination of positive future and positive past events yielded greater memory performance than negative events, as well as receiving higher vividness and plausibility ratings. In addition, simulation of a negative event occurring positively in the future or having occurred positively in the past produced higher memory performance, compared to simulation of a positive event occurring / having occurred negatively. However, participants' predictions for their subsequent memory performance did not reflect their increased tendency to remember positive or could-be / could-have-been positive events neither for future nor past reconstructions. These findings are interpreted in the framework of positivity bias which suggests that people have a tendency towards positivity when simulating future events; and we extend this positivity bias to reconstructions of the hypothetical past events as well.